Timed Automata as a Formalism for Expressing Security: A Survey on Theory and Practice - Arcile, Johan; André, Étienne (ACM computing surveys, 2023)
Timed automata are a common formalism for the verification of concurrent systems subject to timing constraints. They extend finite-state automata with clocks, that constrain the system behavior in locations, and to take transitions. While timed automata were originally designed for safety (in the wide sense of correctness w.r.t. a formal property), they were progressively used in a number of works to guarantee security properties. In this work, we review works studying security properties for timed automata over the past two decades. We notably review theoretical works, with a particular focus on opacity, as well as more practical works, with a particular focus on attack trees and their extensions. We derive main conclusions concerning open perspectives, as well as tool support.